Metabolite variations and antioxidant activity of Muntingia calabura leaves in response to different drying methods and ethanol ratios elucidated by NMR-based metabolomics - Zolkeflee, Nur Khaleeda Zulaikha; Isamail, Nor Amira; Maulidiani, Maulidiani; Abdul Hamid, Nur Ashikin; Ramli, Nurul Shazini; Azlan, Azrina; Abas, Faridah (John Wiley & Sons, 2021)
Introduction Muntingia calabura from the Muntingiaceae family has been documented for several medicinal uses. The combinations of drying treatment and extracting solvents for a plant species need to be determined and optimised to ensure that the extracts contain adequate amounts of the bioactive metabolites.